Pengaruh Latihan Sirkuit Terhadap Kecepatan dan Kelincahan SSB Putra Harapan Dampyak Kabupaten Tegal - Muhammad Faturrahman (YLPK Mahardhika, 2022)
The rationale for this study is that the training speed of the players is still low, and the agility training is poor because the players do not master the soccer game. Circuit training offers many positive changes to your core skills. The purpose of this study was to determine the effectiveness of SSB speed and agility circuit training Putra Harapan Dampyak, Semarang Regency.This study was conducted using a quantitative approach using the